Effect of Calcium Propionate Supplementation on Ruman Fermentation and Blood Biochemical Profile in Dairy Cattle - Ravi, Kumar D; MVAN, Suryanarayana; Devasena, B; Reddy Y, Ravindra; Maram, Harani (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study was aimed to explore the effects of supplementation of different rates of calcium propionate on nutrient utilization, rumen  fermentation pattern and blood biochemical profile of mid lactating dairy cattle. The dairy cows were fed with a common diet of ad  libitum APBN-1 green fodder, concentrate pellet feed and paddy straw. Twenty-four lactating dairy cows (4th to 6th month of lactation)  were randomly divided in to four treatment groups each of six cows. The groups were designated as T1 (control) common diet without  calcium propionate supplementation, whereas the treatment groups T2, T3 and T4 were supplemented with calcium propionate at  the rate of 60 g, 70 g and 80 g/animal/day in addition to the common diet. Feeding trial was carried out for a period of 40 days. The  supplementation of calcium propionate to the dairy cattle had no major changes in the rumen pH within the treatment. In the present  study, there was no significant difference in mean pH values among the dietary treatments, time/hours after feeding and diet x hour  interaction. The mean TVFA (mEq/L) was lowest at 0 h and highest (p
Keywords: calcium propionate, rumen p H, NH3-N, BUN, TVFA